2020
DOI: 10.12973/eu-jer.9.2.865
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of Mathematical Literacy Instruments for Assessment for Learning in Indonesia

Abstract: This study aims to design mathematical literacy instruments that have evidence of content and construct validity and are reliable for use as an assessment for learning. The research involved eight experts as instrument validators and 273 eighth-grade students of junior high school in Yogyakarta Province. The results showed that the ten mathematical literacy items developed had the V Aiken coefficient index calculated from 0.781 to 0.906 (> 0.75). The results of adequacy testing of samples with KMO and Bartlett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The scores of the results of testing the validity and reliability of the instruments were compared with the categorization scale of the test items that follow the Guilford pattern to determine the level of validity and reliability of the test items. The categorization scale intended can be shown in Table 1 (Prihatnawati, Amin, and Muhdhar, 2017;Putra, Husna, and Gunawan, 2018;Suciati et al, 2019;Ardayati and Herlina, 2020) The analysis technique toward trial results of digital test instruments used the calculation of effectiveness percentage. Effectiveness percentage calculation produces a percentage of assessment that was used to provide an interpretation of the trial results of the digital test instruments being developed.…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The scores of the results of testing the validity and reliability of the instruments were compared with the categorization scale of the test items that follow the Guilford pattern to determine the level of validity and reliability of the test items. The categorization scale intended can be shown in Table 1 (Prihatnawati, Amin, and Muhdhar, 2017;Putra, Husna, and Gunawan, 2018;Suciati et al, 2019;Ardayati and Herlina, 2020) The analysis technique toward trial results of digital test instruments used the calculation of effectiveness percentage. Effectiveness percentage calculation produces a percentage of assessment that was used to provide an interpretation of the trial results of the digital test instruments being developed.…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…The validity test results on the item test instruments classified as a very high validity category with a validity score were 0.878, reliability test results classified as high reliability with reliability score were 0.791, and the trial results toward digital test instruments based on Wondershare-Superitem showed good effectiveness with average percentage were 87.12%. The validity and reliability categorization refers to the Guilford pattern scale (Fazlina, 2018;Suciati et al 2019), while the trial results categorization refers to the five-scale effectiveness level (Cheng et al, 2019;Mantasiah, Yusri, and Jufri, 2020).…”
Section: Figure 10mentioning
confidence: 99%
“…Several studies on applying authentic assessments related to students' mathematical competencies have also been carried out (Reyes-Cedeno et al, 2019;Suciati et al, 2018). A study by Fauziah et al (2018) shows that the application of authentic assessment can improve students' mathematics learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The alpha Cronbach test also found that the scale is reliable (.7–.9) according to Guilford’s criteria. 37…”
Section: Discussionmentioning
confidence: 99%
“…The alpha Cronbach test also found that the scale is reliable (.7-.9) according to Guilford's criteria. 37 The initial version scale consists of 31 items turned to 26 items with loading factors ranging from .26 to 1.406 after CFA (see appendix 1 and 2). This implies that a total of 5 The easy access to sexual information and contraceptives makes them less worried about pregnancy risk.…”
Section: Discussionmentioning
confidence: 99%